2019
DOI: 10.3390/ijerph16214284
|View full text |Cite
|
Sign up to set email alerts
|

Newly Qualified Nurses’ Perception of Their Competency Achievement on Leaving University: A Qualitative Study

Abstract: Background: After implementing the Tuning Educational Structures in Europe Project, numerous efforts have been made to define, establish, and evaluate nursing competences. The European Federation of Nurses Association played a key role in enacting the nursing competences included in Directive 2013/55/EU. Nevertheless, assessing competences remains elusive, and there is little research into nurses’ perceptions of the competency training provided by their universities. The purpose of the study was to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…This was confirmed by Wagensteen, Johansson and Nordstrom ( 2008 ) who stated that newly qualified professional nurses experienced the leadership role as challenging because of the lack of preparation with regard to clinical demands and also inability to prioritise the workload, planning and distribution of tasks. Further reasons for this were identified by López-Entrambasaguas et al ( 2019 ) because of the fact that newly qualified professional nurses had not had the opportunity to develop leadership skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was confirmed by Wagensteen, Johansson and Nordstrom ( 2008 ) who stated that newly qualified professional nurses experienced the leadership role as challenging because of the lack of preparation with regard to clinical demands and also inability to prioritise the workload, planning and distribution of tasks. Further reasons for this were identified by López-Entrambasaguas et al ( 2019 ) because of the fact that newly qualified professional nurses had not had the opportunity to develop leadership skills.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted by Benner ( 2001 ) cited in López-Entrambasaguas et al ( 2019 ) studies revealed that the acquisition and development of competences occur along a continuum made up of five levels. This starts with being a novice, passing through an advanced beginner, competent and proficient before finally reaching the fifth stage of advanced competence.…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation showed that CBL-SCT courses combined with the practical characteristics of the profession played an obvious role in improving the training effect, leading to the student nurses in the experimental group significantly improving their professional skills, specialty theory, post competence, and professional quality. The enhancement of the training effect was more beneficial to the rapid improvement of the independent practice ability of student nurses [ 34 ]. Therefore, the CBL-SCT mode can help student nurses to grasp the nursing quality standards firmly at the initial stage of entering the pediatric surgery department, and then to complete their clinical nursing work in practice calmly, orderly, and efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…A partir de este concepto se logran perfiles que definen el rango de acción y escenario de desempeño profesional. Sobre ello el Proyecto Tuning definió, desde el paradigma educativo, los diversos tipos de competencias disciplinares, relativas al saber, ser y hacer, divididas en dos perfiles: competencias genéricas, definidas como generales, transferibles y transversales a la trayectoria formativa, y competencias específicas que identifican el aprendizaje concreto (3,4) .…”
Section: Introductionunclassified